Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1523/jneurosci.4973-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Production in CA1 Neurons Induces MIP-1α Expression, Microglia Recruitment, and Delayed Neuronal Death after Transient Forebrain Ischemia

Abstract: Several studies report microglial accumulation and activation in the CA1 area in response to transient forebrain ischemia (TFI). Here we examine the possibility that free radicals and chemokines mediate the transient activation of microglia. Free radicals are produced primarily in CA1 pyramidal neurons within 2 h of TFI. Administration of trolox, a vitamin E analog, led to the inhibition of free radical production and recruitment of microglia in the CA1 area. In addition, intrahippocampal injection of Fe 2ϩ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Neutrophils and macrophages are recruited into injured brain areas after focal cerebral ischemia, which is significantly reduced in monocyte chemoattractant protein 1 (MCP-1)-deficient mice [52]. Expression of MCP-1 and macrophage inflammatory protein-1-alpha (MIP-1-alpha) is increased in CA1 neurons after TFI and thought to mediate the recruitment of iron-containing infiltrating leukocytes and possibly erythrocytes [57]. Iron can be released from these recruited blood cells and then iron- transferrin is taken up by and accumulates in CA1 neurons over-expressing TfR for a prolonged period of time after TFI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils and macrophages are recruited into injured brain areas after focal cerebral ischemia, which is significantly reduced in monocyte chemoattractant protein 1 (MCP-1)-deficient mice [52]. Expression of MCP-1 and macrophage inflammatory protein-1-alpha (MIP-1-alpha) is increased in CA1 neurons after TFI and thought to mediate the recruitment of iron-containing infiltrating leukocytes and possibly erythrocytes [57]. Iron can be released from these recruited blood cells and then iron- transferrin is taken up by and accumulates in CA1 neurons over-expressing TfR for a prolonged period of time after TFI.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed neuronal degeneration was assessed by histological examination of Cresyl violet-stained brain sections at the level of the dorsal hippocampus collected from animals killed 3 or 7 days after ischemia as previously reported [57]. For quantitative analysis, surviving neurons in the CA1 layer within a 50 9 200 lm rectangular area were counted using an ocular grid within the microscope eyepiece (Olympus Optical Co., Tokyo, Japan).…”
Section: Quantitation Of Neuronal Death In the Ca1mentioning
confidence: 99%
See 1 more Smart Citation
“…Iron-mediated free radical production mediates neuronal death and gliosis in the CA1 area after TFI (Kondo et al, 1995;Wang et al, 2008). Recent studies have shown that oxidative stress is a prominent feature of cerebral endothelial injury after cerebral ischemia (Maier et al, 2006;Jin et al, 2008).…”
Section: Levels Of [mentioning
confidence: 99%
“…Pharmacological treatments seeking to remove free radicals prevent BBB breakdown and neuronal death following focal cerebral ischemia (Kim et al, 2001;Ding-Zhou et al, 2002). Iron ions, serving as transition metal molecules catalyzing hydroxyl radical production via the Fenton reaction and the Haber-Weiss cycle, accumulate in neurons, astrocytes, and microglia in hippocampal CA1 areas, after occurrence of transient forebrain ischemia (TFI), and cause neuronal death and gliosis (Kondo et al, 1995;Wang et al, 2008). In the present study, we explored the possibility that iron-mediated free radical production mediates endothelial cell damage and BBB opening in the hippocampal CA1-2 regions, following TFI.…”
Section: Introductionmentioning
confidence: 99%